Noise Figure and Pump Reflection Power in SMF-Reach Optical Fibre for Raman Amplification - Boiyo, Duncan; Rotich, E. K.; Gamatham, R. R. G.; Leitch, A.W. R. (My University, 2015)
We investigate both experimentally and by simulation the Noise Figure (NF) and pump reflection power of a Distributed Fibre Raman Amplifier (DFRA) as a function of pump power and fibre length, at different pump configurations. A DFRA of lengths 25 km and 50 km has been experimentally designed using Single Mode Reach Fibre (SMF-Reach) with an attenuation of 0.20 dB/km. Two pumping techniques namely Co-pumping and counter pumping have been used. It was found that the increase in fibre length, lead to increase in the NF irrespective of the pumping technique used. A NF of -2.2 dB and -1.9 dB was achieved experimentally for Co- and Counter pumping schemes respectively, for a 25 km fibre at 23 dB pump power. For a 50 km fibre, a NF of -1.8 dB and -0.7 dB was obtained for the two pump configurations respectively, under the same pump power. Pump reflection power varied inversely with gain and directly with fibre length. This work recommends Co-pumping technique in signal transmission due to its low NF and pump reflection power.
Keywords: Raman Fibre amplifier; Noise Figure; Optical Signal to Noise Ratio